Улитка на склоне: фантастический роман / Аркадий и Борис Стругацкие - Стругацкий Аркадий Натанович (АСТ, 2009)
Экземпляры: аб. (20230526) / Инвентарный номер: 63668 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 87 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445.1